When we talk about time, we mean many different things: employing visual mapping to think through more-than-human temporalities in participatory design - Zohar, Hadas; Simeone, Luca; de Götzen, Amalia; Morelli, Nicola (Frontiers in Communication, 2024)
In recent years, the scope of participatory design has broadened to encompass perspectives and approaches beyond the human realm. This expansion requires considering multiple aspects to fully capture ‘more-than-humans’ diversity and concerns. One approach to tackle this multifaceted challenge is by examining it through the lens of time. However, the temporal dynamics of more-than-human entities remain relatively unexplored within participatory design. This paper investigates the potential of visual mapping to aid stakeholders engaged in participatory design processes that incorporate more-than-human perspectives in navigating the complex dimensions of more-than-human time. The findings demonstrate how visual mapping can facilitate thinking beyond linearity, developing awareness of workshop-related temporality, making time concrete, understanding the ‘far lense’ through the ‘near lense’, comprehending time’s relationality, unfolding time and considering multiple timespans simultaneously. Based on these findings, the paper suggests that visual mapping can help understand more-than-human temporalities in participatory design by thinking through them as a reflective practice.